Ecological science and sustainability for the 21st century - Palmer, Margaret A; Bernhardt, Emily S; Chornesky, Elizabeth A (Himalayan Journal of Sciences, 2007)
Through the work of international public health organizations and advancements in the biological and technological sciences, substantial progress has been made in our ability to prevent, control, locally eliminate, and in one case eradicate infectious diseases. Yet each successful control or local elimination has been met with the emergence of new pathogens, the evolution of novel strains, or different epidemiological circumstances that have limited or reversed control methods. To respond to the increasing threat of emerging infectious diseases and bioterrorism it is vital that we design and implement efficient programs that prevent and control infectious pathogen transmission. The theoretical tools of ecology and epidemiology may be the cornerstone in constructing future programs aimed at preventing and controlling infectious diseases throughout the world.Reprinted with permission from Frontiers in Ecology and the Environment, Vol 3, Issue No 1, page 4–11, issue of February 2005. Copyright © 2005 by The Ecological Society of America.Himalayan Journal of Sciences 3(5) 2005 p.25-32